Impact of Pharmacotherapy to decrease Interleukin-6 in patients with chronic rhinosinusitis without nasal polyp - Lina Marlina; Sinta Sari Ratunanda; Teti Madiadipoera (Oto Rhino Laryngologica Indonesiana, 2020)
Background: Chronic rhinosinusitis (CRS) is an inflammation of the nasal and paranasal sinuses mucosa, ongoing for more than 12 weeks. Even now it still creates socioeconomic problem in both developed and developing countries. Pharmacotherapy administration is essential for decreasing the severity of symptom, improving quality of life, and decreasing interleukin (IL)-6 level. Objective: To find out the effect of pharmacotherapy on severity of the symptom, quality of life, and IL-6 level. Method: Randomized clinical trial with pre and posttest design, on 20 CRS without polyp patients, divided into two groups based on skin prick test results. Both groups were equally treated with nasal irrigation, nasal corticosteroid, and antibiotic amoxicillin clavulanate for 14 days. All subjects were assessed for Visual Analog Scale (VAS) score, nasoendoscopy (NE) score, Sinonasal Outcome test (SNOT)-22, and IL-6 level. Statistical analysis was performed with Mann Whitney and Wilcoxon methods. Result: There were significant differences in total analysis results on VAS scores, NE scores, SNOT-22, and IL-6 levels in both groups, with values p<0.05. There was improvement in all variables after pharmacotherapy, but there was no significant difference between the case and control groups, with values p>0.05. Conclusion: Pharmacotherapy in both groups resulte’ in reduced severity of symptoms, improved quality of lives, and decreased IL-6 levels.Keywords: Interleukin-6, pharmacotherapy, chronic rhinosinusitis without polyp, quality of life ABSTRAK Latar belakang: Rinosinusitis kronik (RSK) merupakan inflamasi pada mukosa hidung dan sinus paranasal, yang berlangsung selama lebih dari 12 minggu. Hingga saat ini masih memengaruhi sosioekonomi di negara maju maupun negara berkembang. Pemberian farmakoterapi sangat penting untuk memperbaiki derajat gejala, meningkatkan kualitas hidup, dan menurunkan kadar interleukin (IL)-6. Tujuan: Mengetahui pengaruh pemberian farmakoterapi terhadap perbaikan derajat gejala, peningkatan kualitas hidup, dan penurunan kadar IL-6. Metode: Penelitian kuasi eksperimental, label terbuka pra dan pascaterapi, pada 20 penderita RSK tanpa polip, dibagi dua kelompok berdasarkan hasil uji tusuk kulit. Perlakuan pada kedua kelompok sama, diberikan irigasi hidung, kortikosteroid intranasal, dan antibiotik amoksisilin klavulanat selama 14 hari. Penelitian dilakukan dengan menilai skor Visual Analog Scale (VAS) gejala hidung, skor nasoendoskopi (NE), Sinonasal Outcome test (SNOT)-22, dan kadar IL-6. Analisis statistik menggunakan metode Mann Whitney dan Wilcoxon. Hasil: Didapati perbedaan bermakna pada hasil analisis total pada skor VAS gejala hidung, skor NE, SNOT-22, dan kadar IL-6 pada kedua kelompok dengan nilai p<0,05. Didapati perbaikan pada semua variabel setelah 14 hari pemberian medikamentosa maksimal, namun tidak terdapat perbedaan bermakna antara kedua kelompok dengan nilai p>0,05. Kesimpulan: Pemberian farmakoterapi pada kedua kelompok memberikan hasil berupa perbaikan derajat gejala, peningkatan kualitas hidup, dan penurunan kadar IL-6.